1) (2a + 5b) + (8a - 11b) + (9b - 5a) = 2a + 5b + 8a - 11b + 9b - 5a =
= (2a + 8a - 5a) + (5b - 11b + 9b) = 5a + 3b
2) (3х + 10у) – (6х + 3у) + (6у – 8х) = 3х + 10у – 6х - 3у + 6у – 8х =
= (3x - 6x - 8x) + (10y- 3y + 6y) = - 11x + 13y
3) (8с² + 3с) + (- 7с² – 11с + 3) – (- 3с² – 4) = 8с² + 3с - 7с² – 11с + 3 + 3с² + 4 =
= (8c² - 7c² + 3c²) + (3c - 11c) + (3 + 4) = 4c² - 8c + 7
4) (2р² + 3рс + 8с²) – (6р² – рс – 8с²) = 2р² + 3рс + 8с² – 6р² + рс + 8с²=
= (2p² - 6p²) + (8c² + 8c²) + (3pc + pc) = - 4p² + 16c² + 4pc
5) 10х² – (7ах – 5х² + 8а²) + (6ах – 4а²) = 10х² – 7ах + 5х² - 8а² + 6ах – 4а²=
= (10x² + 5x²) + (- 7ax + 6ax) + (- 8a² - 4a²) = 15x² - ax - 12a²
Объяснение:
1) 8у - 3(2у - 3) = 7у - 2(5у + 8), 2) 5(2у - 9) + 6у = 4(3у - 2) - 21,
8y - 6y + 9 = 7y - 10y - 16, 10у - 45 + 6у = 12у - 8 - 21,
2y + 9 =-3у - 16, 16у - 45 = 12у - 29,
2у + 3у = -16 - 9, 16у - 12у = -29 + 45,
5y = -25, 4у = 16,
у = -25 : 5, у = 16 : 4,
y = -5; у = 4;
№ 2. 1) 5(3 - 2у) - 4(9 - у) = 3(у + 5),
15 - 10y - 36 + 4y = 3y + 15,
-6y - 21 = 3у + 15,
-6у - 3у = 15 + 21,
-9y = 36,
у = 36 : (-9),
y = -4;
2) 14(2х - 3) - 5(х + 4) = 2(3х + 5) + 5х,
28x - 42 - 5x - 20 = 6x + 10 + 5x,
23х - 62 = 11х + 10,
23x - 11x = 10 + 62,
12x = 72,
х = 72 : 12,
x = 6;
3) 9(3х - 7) + 3(8х - 11) = 3(9х + 8),
27x - 63 + 24x - 33 = 27x + 24,
51x - 96 = 27х + 24,
51х - 27х = 24 + 96,
24x = 120,
х = 120 : 24,
x = 5;
4) 6(7х - 11) - 13(х - 6) = 14(2х + 1),
42x - 66 - 13x + 78 = 28x + 14,
29x + 12 = 28х + 14,
29x - 28 х = 14 - 12,
х = 2;
№ 3. 1) 1,2х + 7 = 2x + 3, (здесь, видимо, пропущен х)
1,2x - 2х = 3 - 7,
-0,8x = -4,
х = -4 : (-0,8),
x = 5;
2) 8,3 - 2,1х = 2(1,5х + 11,8),
8,3 - 2,1х = 3х + 23,6,
-2,1х - 3х = 23,6 - 8,3,
-5,1х = 15,3,
х = 15,3 : (-5,1),
х = -3;
3) 9(13 - 0,8х) + 6,7 = 7,1х - 5,
117 - 7,2х + 6,7 = 7,1х - 5,
-7,2х + 123,7 = 7,1х - 5,
-7,2х - 7,1х = -5 - 123,7,
-14,3х = -128,7,
х = -128,7 : (-14,3),
х = 9.
7x+4x -12x< 4-8
-x<-4
x>4
(4;+♾)